ISLAMIC AND ARABIC ACADEMIC RESEARCH IN MALAYSIA: A BIBLIOMETRIC ANALYSIS OF PUBLICATION TRENDS AND SCHOLARLY IMPACT (2005-2025) - Yasin, Muhammad Muthi’ul Haqq Fatah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study investigates bibliometric trends in Islamic and Arabic academic research in Malaysia from 2005 to 2025, addressing the increasing scholarly interest and the need to map the intellectual landscape of this field. Despite the global significance of Islamic and Arabic studies, there remains a lack of comprehensive quantitative analysis specific to Malaysia’s research output. To fill this gap, the research employed a systematic methodology, utilizing the keywords "Islamic," "Arabic," and "research" to retrieve relevant literature from the Scopus database. Data cleaning and refinement were conducted using OpenRefine, while Scopus Analyzer and VOSviewer software facilitated in-depth bibliometric analysis, including co-authorship, citation, and keyword mapping. The final dataset comprised 310 peer-reviewed journal articles, ensuring a focused and high-quality sample. The analysis revealed notable growth in publication volume over the two decades, with a strong emphasis on interdisciplinary themes such as Islamic economics, education, and language studies. Co-authorship networks highlighted Malaysia’s central role in regional and international collaborations, while keyword co-occurrence analysis identified evolving research hotspots and thematic clusters. The results underscore the dynamic and interconnected nature of Islamic and Arabic academic research in Malaysia, providing valuable insights into prevailing trends, influential contributors, and emerging areas of interest. In conclusion, this bibliometric study not only charts the development and scholarly impact of the field but also offers a foundation for future research directions and policy formulation in Islamic and Arabic studies.